Prospectus 2010 : Preparation for Life / Department of Corporate Communications, UiTM - Department of Corporate Communications, UiTM (Department of Corporate Communications, UiTM, 2010)
UiTM is unique. The breadth and balance of the courses we offer marks UiTM from the crowd. There are 24 faculties and centres, as well as 13 state campuses offering programmes that spread equally across the Arts, Social Science, Businesss and Science & Technology. We have about 140,000 students and an unparralelled breadth of 315 programmes for you to choose from. The university is also outward looking, and is actively engaged in innovative and exciting developments. A large proportion of our academics are "research active" and UiTM has strong research collaborations nationally and internationally. This means that you will be surrounded by academics who are in touch with developments in leading research centres around the world.